A bibliometric and social network analysis of pelvic organ prolapse during 2007–2016. Issue 5 (May 2018) - Huang, Feng; Zhou, Quan; Leng, Bing‐Jie; Mao, Qiao‐Ling; Zheng, Li‐Min; Zuo, Man‐Zhen
Abstract : Background: : Pelvic organ prolapse (POP) seriously affects the life quality of old females. In the present work, we described the knowledge structure of POP in a macroscopic view, and summarized the recent research focus. Methods: : Candidates were identified through reading and screening publications from PubMed database with a MeSH term of "pelvic organ prolapse" during 2007–2016. Relevant journals and journal‐affiliated countries were extracted, and essential information, such as the number of publication of each year, first authors and MeSH/subheading words, was analyzed with BICOMB. In addition, highly‐frequent MeSH/subheading words were determined and classified, and co‐occurrence matrices were produced accordingly. Finally, social network was utilized to analyze the knowledge structure. Results: : A total of 3294 publications of POP were retrieved from 364 journals. The publication of POP had a significant downward trend since the beginning of 2015. POP articles published in American and British journals were significantly more compared with other countries. The co‐occurrence matrices of 37 × 37 and 55 × 55 were produced by the highly‐frequent MeSH/subheading words, and then the social network analysis was performed based on them. Conclusion: : These publications on POP were mainly from the developed countries. Surgical treatment of POP was a hot topic of POP research in recent 10 years.